QUILLBOT INTEGRATION IN THE LEARNING OF ENGLISH WRITING SKILLS (PERCEPTION OF BUSINESS MANAGEMENT STUDENTS) - Bakri, Irfiani; Wulandari, Mega Fitri; Amalia. S, Reski; Rut, Walangitan Melania (International Journal of Research on English Teaching and Applied Linguistics, 2024)
The aim of this research is to find Business Management students perceptions regarding the use of Quillbot as a writing tool for English writing skill improvement This research employs a qualitative case study approach. The research instruments were questionnaire and interview. The questionnaire closed-ended questions utilizing a four-point Likert scale (ranging from Strongly Agree to Strongly Disagree) shared via Google Forms. Additionally, semi-structured interview questions were formulated based on the questionnaire responses. The data obtained from the closed-ended questionnaire questions are quantitatively was analysed through frequency calculations. The total of the population are 40 business management students. The results indicate that AI has the capacity to enhance writing skills by aiding in idea generation, improving critical thinking, preventing plagiarism, and elevating academic writing quality. Consequently, integrating AI into higher education can effectively enhance the quality of writing education, aligning with the digital era's advancements and optimizing the learning process for effectiveness and efficiency.